Continuous sunitinib schedule in advanced platinum refractory thymic epithelial neoplasms: A retrospective analysis from the ThYmic MalignanciEs (TYME) Italian collaborative group. (October 2022) - Antonarelli, Gabriele; Corti, Chiara; Zucali, Paolo Andrea; Perrino, Matteo; Manglaviti, Sara; Lo Russo, Giuseppe; Varano, Gianluca Maria; Salvini, Piermario; Curigliano, Giuseppe; Catania, Chiara; Conforti, Fabio; De Pas, Tommaso
Abstract: Background: Thymic epithelial tumors (TETs) are rare diseases, with diverse clinical behaviour and prognosis. Intermittent dosing sunitinib represents the gold-standard systemic treatment following platinum-based chemotherapy. To ensure more homogeneous drug exposure, continuous daily dosing (CDD) sunitinib is utilised in other malignancies; however, no data exist in patients with TETs. Methods: We retrospectively examined data from patients with platinum-resistant TETs receiving CDD sunitinib 37.5 mg between 1 May 2017 and 31 May 2022 within the Italian collaborative group for ThYmic MalignanciEs. Primary end-points were median progression-free survival, overall response rate (ORR), median duration of response and major treatment-related adverse events. Results: A total of 20 consecutive patients (12 thymic carcinoma [TC], 6 B3, and 2 B2 thymoma) were evaluated. Among the 19 patients evaluable for response, ORR was 31.6% (95% CI, 12.5%–56.5%). Among patients with TC, one complete response, four partial responses, and four stable diseases were observed (ORR 41%).The overall median progression-free survival was 7.3 months (95% CI, 4.5–10.3): 7.3 months (95% CI, 4.4–NA) within patients with thymoma and 6.8 months (95% CI, 2.8–10.3) in patients with TC; median duration of response was 10.3 months (95% CI, 2.8–NA). CDD was associated with a manageable toxicity profile. Six patients (30%) experienced >G2 toxicity, nine required dose reduction and three discontinued treatment due to adverse events. Conclusions: CDD sunitinib showed a relevant antitumor activity and confirmed a good toxicity profile. Similar effectiveness and a better toxicity profile as compared with intermittent dosing historical data suggest that this schedule should be considered. Highlights: Intermittent sunitinib is used in platinum-refractory thymic epithelial tumours. Continuous daily dose (CDD) sunitinib is used other cancers; no data exist in thymic epithelial tumours. We retrospectively analysed data from patients receiving off-label CDD sunitinib. CDD sunitinib schedule showed clinical efficacy and a favourable toxicity profile.